2016
DOI: 10.1016/j.addbeh.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Altered developmental trajectories for impulsivity and sensation seeking among adolescent substance users

Abstract: A number of studies have associated impulsivity and sensation seeking with level of substance use and risk for developing a substance use disorder. These relationships may be particularly apparent during adolescence, when developmental changes in impulsivity and sensation seeking occur at the same time as increased opportunities for substance use. To examine this, the current study measured impulsivity and sensation seeking from pre-adolescence to mid-adolescence in a sample of youth, the majority of whom were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 42 publications
9
33
2
10
Order By: Relevance
“…In line with this notion, we found that adolescent rats were less able to inhibit inappropriate responses that led to a timeout rather than a food reward compared to their adult counterparts. This suggests adolescents have higher levels of impulsive action relative to adults, which is consistent with another study in rats that used similar methods (Burton & Fletcher 2012) and with human studies showing a relative deficit in inhibitory control during adolescence (Steinberg et al 2008;Shulman et al 2014;Charles et al 2016). However, we did not find any evidence for an age difference in impulsive choice, which is in contrast to human studies (Steinberg et al 2009;Achterberg et al 2016).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In line with this notion, we found that adolescent rats were less able to inhibit inappropriate responses that led to a timeout rather than a food reward compared to their adult counterparts. This suggests adolescents have higher levels of impulsive action relative to adults, which is consistent with another study in rats that used similar methods (Burton & Fletcher 2012) and with human studies showing a relative deficit in inhibitory control during adolescence (Steinberg et al 2008;Shulman et al 2014;Charles et al 2016). However, we did not find any evidence for an age difference in impulsive choice, which is in contrast to human studies (Steinberg et al 2009;Achterberg et al 2016).…”
Section: Discussioncontrasting
confidence: 57%
“…Notably, behavior becomes more controlled and less impulsive from adolescence to adulthood (Steinberg et al 2008;Shulman et al 2014;Charles et al 2016), perhaps as a result of maturation within the PFC and striatum (Ernst et al 2009), and this occurs in a sex-specific fashion. For example, girls have better impulse control by the end of adolescence (Shulman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that sensation seeking is associated with elevated substance use due to a higher level of physiological reward response for substance use behaviors (Bardo, Donohew, & Harrington, 1996; Kaynak et al, 2013) due to immaturity of the prefrontal regions responsible for cognitive control. Additionally, earlier initiation of substance use has been posited to mediate the association between sensation seeking and substance use in later adolescence and adulthood (Charles et al, 2016; Steinberg, 2008). Studies examining sensation seeking and substance use longitudinally have found that increases in sensation seeking are associated with increases in substance use during adolescence (Crawford et al, 2003; MacPherson et al, 2010) and young adulthood (Knafo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar changes have been observed in patients addicted to psychoactive substances [21]. Literature unanimously con rms that the limbic system plays an essential role in these processes [12,22], but the question whether the limbic system is overactivated or inhibited is still disputable.…”
Section: Neuroanatomical Substrate and Mechanisms Of Emergence Of Icdmentioning
confidence: 50%